TANTANGAN TUGAS, PENGARUH BEBAN KERJA SERTA TANGGUNG JAWAB KERJA DALAM KEHIDUPAN SEORANG POLISI - Adelia Citra; Nurul Janah, Salsabilla Citra, Zahwa Kania Putri, Tugimin Supriyadi (CV. ADIBA AISHA AMIRA, 2024)
In the context of responsibility, they are not only responsible for law enforcement, but also for the welfare of the community they serve. Police responsibilities include protecting human rights, preventing crime, handling crises, and supporting fair judicial processes. This research aims to determine or explore the dynamics of workload and responsibilities faced by police in carrying out their duties. Police workload has become a significant subject of concern in law enforcement, as they are faced with a variety of tasks that include patrolling, crime investigations, apprehension of criminals, as well as administrative tasks such as completing reports and administering cases. The challenges that police officers face in carrying out their workload and responsibilities include limited resources, psychological stress, and risks to personal safety. However, research also shows that strong organizational support, ongoing training, and stress management strategies can help police overcome these challenges more effectively and that a better understanding of police workload and responsibilities is an important step in improving the quality of enforcement services law. law and police welfare. With a holistic approach and the right support, the police can be more effective in carrying out their duties to maintain community peace and achieve justice.